Cornell University Press, est. 1869 : our first 150 years - Laun, Karen M., 1970- (Cornell University Press, 2019)
"This book is a history of Cornell University Press since its establishment in 1869 and a list of 150 notable books the press has published. It is being issued to mark the 150th anniversary of the press in 2019"--